2023
DOI: 10.2478/rem-2023-0009
|View full text |Cite
|
Sign up to set email alerts
|

One year later: digitalized higher education in pandemic times. An international study of higher education faculty’s response

Abstract: The paper describes the international research conducted in collaboration between the University of Padova, University of North Texas, and Windesheim University of Applied Sciences. The study explores how higher education faculty involved in professionalizing courses for the educational area perceive the pandemic-induced transition to digitalized education (DE), after one year of experience with it. This paper introduces the second phase of a research study that began as early as spring 2020, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, Watermeyer et al (2021) found that at-home work "was viewed as actually contributing to work intensification and the erosion of work-life balance," with the deterioration of traditional boundaries between home and work lives contributing to "hyper-professionality" and working to excess (p. 633). Similarly, Trevisan and De Rossi (2023) found that the "pervasiveness of work time in personal life" was the greatest challenge identified by their survey participants (p. 68). Meanwhile, Littlejohn et al (2021) observed that "working from home fundamentally changes each educator's capacity to teach" (p. 4) as well their interactions with colleagues and students; this can be especially challenging for those with caregiving responsibilities and those who lack dedicated at-home office space (p. 9).…”
Section: Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, Watermeyer et al (2021) found that at-home work "was viewed as actually contributing to work intensification and the erosion of work-life balance," with the deterioration of traditional boundaries between home and work lives contributing to "hyper-professionality" and working to excess (p. 633). Similarly, Trevisan and De Rossi (2023) found that the "pervasiveness of work time in personal life" was the greatest challenge identified by their survey participants (p. 68). Meanwhile, Littlejohn et al (2021) observed that "working from home fundamentally changes each educator's capacity to teach" (p. 4) as well their interactions with colleagues and students; this can be especially challenging for those with caregiving responsibilities and those who lack dedicated at-home office space (p. 9).…”
Section: Literature Reviewmentioning
confidence: 92%
“…In Canada, Danyluk and Burns (2021) surveyed full-time and contract university faculty to examine and compare their experiences during the transition. A later study by Trevisan and De Rossi (2023) examined the impacts on education faculty in Italy and the United States, a year after moving to digitized instruction. Although the latter three studies were smaller in scope, with each focusing on a smaller number of educators at one or two universities, the larger study by Watermeyer et al surveyed 1148 academics at universities throughout the UK.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation